ANALISIS KEPUASAN WISATAWAN TERHADAP PANTAI BAHARI JAWAI DI KABUPATEN SAMBAS - Maryono Maryono; Beryaldi Agam; Oktavia Nurmawaty Sigiro (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2021)
Marine ecotourism is the potential of an area to improve the welfare of coastal communities. The Jawai Marine Tourism Beach, located in Sambas Regency, is a tourist location developed from self-help at the start of the pandemic of COVID-19. In its development, the management of this area is still making continuous improvements in marine tourism services in fulfilling the wishes and needs of visitors. This research aims to determine the level of visitor satisfaction based on the Customer Satisfaction Index (CSI) and the attribute importance level based on the Importance Performance Analysis (IPA). This research has conducted from March-July 2021 at The Bahari Coast of Jawai Sambas Regency. Research methods are quantitative research methods. The research method is a quantitative research method with accidental sampling techniques. Data was obtained by distributing 220 questionnaires to visitors. The results showed that the CSI data was 69.21%, which means that the manager's performance has not met the needs and desires of visitors. Based on the results of data processing that has been carried out with IPA, several attributes must be improved and improved. The attributes which need to be improved to upgrade the service quality of the Jawai Marine Tourism Park are 1). Accommodation costs such as toilet, parking, and entrance fees; 2). Prices of food, drinks, and souvenirs. All stakeholders are expected to contribute to the development of marine ecotourism in the form of ideas, ideas, energy, thoughts, and financial assistance.